Development and characterization of a recombinant Senecavirus A expressing enhanced green fluorescent protein - Huang, Weihong; Chen, Yongjie; Xu, Ting; Xiong, Ting; Lv, Yadi; Liu, Dingxiang; Chen, Ruiai (Frontiers in Microbiology, 2024)
Senecavirus A (SVA), belonging to the genus Senecavirus in the family Picornaviridae, is an emerging pathogen causing vesicular disease in pigs. The main clinical manifestations of SVA infection include high mortality in neonatal piglets, skin ulceration, and vesicular lesions. So far, there is no commercially available vaccines or drugs against SVA. Construction of SVA infectious clones carrying reporter genes will help understand the characteristics of SVA and promote vaccine development. In this study, we established a reverse genetics system for a local SVA isolate and used it to rescue a recombinant SVA, rSVA-eGFP, expressing the enhanced green fluorescent protein (eGFP) by inserting eGFP, GSG linker and the P2A sequence between 2A and 2B genes. We found that rSVA-eGFP exhibited a high replication efficiency comparable to the parental virus, was able to express the eGFP reporter efficiently and stable in maintaining the reporter gene up to six rounds of serial passages in BHK-21 cells. In mice, rSVA-eGFP also showed similar replication kinetics and pathogenicity to the parental virus, both causing mild lung lesions. In addition, a high-throughput viral neutralization assay was developed using eGFP as a surrogate readout in a fluorescence-based direct titration (FBT) assay based on rSVA-eGFP, facilitating rapid and accurate determination of the neutralizing antibody (nAb) titers. The successful establishment of an SVA reverse genetics system and the rescue of rSVA-eGFP would create a powerful tool for future studies of SVA replication mechanisms and pathogenicity as well as for antiviral development.